INFLUENCE OF MENOPAUSE ON BLOOD PRESSURE DIPPING IN WOMEN WITH METABOLIC SYNDROME: A CASE-CONTROL STUDY - D. A. Anichkov; N. A. Shostak (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study if menopause influences the blood pressure (BP) decrease level during nighttime in women with metabolic syndrome. Methods. 84 women with metabolic syndrome are examined, from them 52 are in postmenopause (average age is 56 [SD 5] years) and 32 are in premenopause (average age is 44 [5] years). Anthropomorphic measurements were made, levels of office BP and heart rate were assessed, ambulatory BP monitoring was carried out, lipids and glucose of blood serum were studied. Results. Clinical parameters, characterizing metabolic syndrome, didn’t vary between the groups. Number of patients with insufficient decrease of BP in postmenopausal women didn’t differ significantly from the number of such women in premenopausal period (for systolic BP: 64% versus 52%, p=0,288; for diastolic BP: 34% versus 42%, p=0,469). Nevertheless, when evaluating the level of systolic BP decrease during nighttime as continuous variable, significant differences between groups are revealed (M±SEM [95% CI]: 4.4±1.5% [1.4-7.3] in postmenopausal women versus 11.3±1.7% [7.9-14.8] in premenopausal women, p=0,011). Conclusion. Postmenopause associates with insufficient systolic BP decrease during nighttime in women with metabolic syndrome.